Tanzania manufacturing sector in response to trade liberalization: A case of pharmaceutical manufacturing - Gesoreka, George (Mzumbe University, 2026)
A dissertation submitted to Dar es Salaam Campus College in the partial fulfillment for the award of Masters of Business Administration (MBA) in Mzumbe University